KEJADIAN HIPERTENSI BERHUBUNGAN DENGAN POLA MAKAN DI RSUD DR. R GOETENG TAROENADIBRATA PURBALINGGA - Suci Khasanah (Universitas Harapan Bangsa Purwokerto, 2014)
Hypertension is a condition in which blood pressure exceeds normal limits. Hypertension raises morbidity and mortality is high. Hypertension disease arises due tothe interaction of various risk factors a person has. One of the risk factors of hypertensionis diet. The purpose of this study was to determine the relationship of diet and the incidence ofhypertension in inpatient medicine dr. R Goeteng Taroenadibrata Purbalingga. This study is a case control study using a quantitative approach. The data wereobtained using a questionnaire. Samples were 33 clients hospitalization in inpatientmedicine dr. R Goeteng Taroenadibrata Purbalingga. Statistical test using frequencydistribution and chi square test with significance Î± = 0.05. The results showed the majority of respondents who have hypertension are clients aged40-50 years, female, obese, and have diets are at risk. The results also showed asignificant relationship between the diet and the incidence of hypertension in which p =0.000 (p <0.05) with a risk estimate of 5.714. The conclusion from this research that the clients who have diets are at risk of having atendency of 5.714 times more likely to have hypertension compared with respondents whohave diets are not at risk. Keywords: Hypertension, Diet, Risk Factors of HypertensionHypertension